PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENERAPKAN METODE MEMBACA AL-QUR’AN SISWA DI SD NEGERI 03 PENDAWAN DUSUN PENDAWAN DESA TANGARAN TAHUN 2021/2022 - Dini Fitriani; Aslan; Eliyah (TARBIYATUL ILMU: Jurnal Kajian Pendidikan, 2024)
This research aims to determine the problem of the low reading ability of students in elementary schools, especially at SD Negeri 03 Pendawan. At this school, Islamic religious education teachers in delivering learning material use several methods to make it eaiser for the teachers to convey learning material to students. This research is descriptive qualitative in the nature and uses data collection techniques by interviews, observation and documentation. The research result show: 1. Theachers in delivering teaching material to students use several methods according to need according to the needs of the students. Examples often use are : the iqra’ methods and the Jibril method. Apart from using several methods, teachers also play an important role during the learning process. There are several teachers roles that are also apllied during the teaching process, for example: 1. Teacher as a learning resource, 2. Teacher as facilitator, 3. Teacher as administrator, 4. Teacher as demonstrator, 5. Teacher as guide, 6. Teacher as motivator, and 7. Teacher as evaluator.